STEM Learning for Enhancing Self-Efficacy and Control of Variables in Prospective Elementary Teachers: A Systematic Review for Quality Science Education - Ni Putu Murniasih S; Supriyatman; Afadil; Citra Dewi; Sarintan Kaharu; Nunuk Haryanti (Postgraduate, University of Mataram, 2026)
The objective of this study is to investigate how STEM (Science, Technology, Engineering, and Mathematics) education contributes to enhancing self-efficacy and control-of-variables strategy (CVS) skills among prospective elementary school teachers, using a Systematic Literature Review (SLR) methodology. This research examined 15 well-regarded international articles that were published between 2020 and 2025 and are indexed by Scopus. To guarantee a systematic, transparent, and responsible review process, the identification, selection, and inclusion of literature were carried out in accordance with PRISMA guidelines. The findings concerning STEM learning models, instructional strategies, and their effects on the psychological and cognitive aspects of prospective teachers were synthesized using thematic analysis. Studies show that STEM approaches based on inquiry, project-based learning, and engineering design consistently improve prospective teachers' self-efficacy in science teaching and strengthen their ability to regularly control variables in experiments. Furthermore, the implementation of the Flipped Classroom model and the integration of digital technology contributes to meaningful learning experiences (mastery experiences), enhanced collaboration, and the development of analytical thinking and problem-solving skills. However, several challenges remain, such as the gap between theory and practice, differences in program duration, and limitations in the development of computational literacy. Overall, STEM learning contributes to preparing prospective elementary school teachers who are confident, reflective, and competent in designing inquiry and technology based science lessons to support the creation of quality science education.